The Effect of Reynolds Number on Jet in Asymmetric Co-Flows: A CFD Study - Ziyan Teng; I. A. Sofia Larsson; T. Staffan Lundström; B. Daniel Marjavaara (International Journal of Chemical Engineering)
In rotary kilns in grate-kiln systems for iron ore pelletizing, a long and stable jet flame is needed to ensure a high quality of the pellets. The primary jet issuing from the nozzle interacts with two asymmetric co-flows creating a very complex flow. In order to better understand and eventually model this flow with quality and trust, simplified cases need to be studied. In this work, a simplified and virtual model is built based on a down-scaled kiln model established in a previous experimental work. The aim is to numerically study the jet development as a function of position and Reynolds number (Re). The numerical simulations are carried out with the standard k-ε model, and quite accurate velocity profiles are obtained while the centerline decays and spreading of the passive scalars are over predicted. The model is capable of predicting a Re dependency of the jet development. With increasing Re, the jet is longer while it generally decays and spreads faster resulting from the stronger shear between the jet and co-flows and the stronger entrainment from the recirculation zone. This recirculation found in the simulations restrain the momentum spreading in the spanwise direction, leading to a slower velocity spreading with higher Re. For further validation and understanding, more measurements in the shear layer and simulations with more advanced turbulence models are necessary.